Fabrication and properties of tricalcium phosphate/barium hexaferrite composites - Narumon Lertcumfu (2018)
Beta-tricalcium phosphate based composites containing particles of barium hexaferrite were fabricated. The beta-tricalcium phosphate fine powder was synthesized from egg shell and Ca 2 P 2 O 7 by a solid-state reaction technique. Effects of barium hexaferrite additive (0-3 vol%) on the properties of the composites were investigated. All samples showed a main phase of β-tricalcium phosphate, characterized by X-ray diffraction technique. The additive inhibited grain growth, but enhanced hardness of the composites. M-H hysteresis loops also showed an improvement in the magnetic behavior for higher barium hexaferrite content samples. However, in vitro bioactivity test indicated that the 2 vol% sample may be suitable for biological applications. © 2012 Elsevier Ltd and Techna Group S.r.l.